Development and properties of synaptic mechanisms in a network of rat hypothalamic neurons grown in culture - Swandulla, Dieter; Misgeld, Ulrich (Journal of neurophysiology, 1990)
1. Dissociated neurons from embryonic rat hypothalamus (E14-15) were cultured on a glial background monolayer for up to three months. Dendrites of cells 7-14 days in culture (DIC) intracellularly stained with the fluorescent dye Lucifer yellow were thin and smooth, and multiple growth cones could be observed. The length of the dendrites of older cells did not differ much, but dendrites were thicker and branched more profoundly, forming a complicated network. Growth cones were rare, but few spine-like protrusions could be observed. 2. Randomly occurring depolarizing potentials were recorded in 60% of the cells 7-14 DIC and in 90% of the cells 21 DIC. Activity became phasic when the gamma-aminobutyric acid (GABA) antagonists picrotoxin or bicuculline were applied. After 21 DIC the majority of the cells showed burst discharges, whereas only approximately 10% of the cells 7 DIC exhibited bursting. 3. With low [Cl] in the recording pipette, spontaneous activity consisted of hyperpolarizing and depolarizing potentials at -40-mV membrane potential. Some spontaneous activity persisted with Na channels blocked by tetrodotoxin (TTX, 0.3-1 microM), and when reducing the external [Ca]o from 5 to 0.3 mM. Picrotoxin blocked part of the activity, and the remaining activity was blocked by kynurenic acid. 4. Bursts of action potentials were superimposed on rhythmically occurring clusters of excitatory synaptic potentials (EPSPs), which had a steep rising phase and decayed within hundreds of milliseconds. Bursts of similar appearance could be triggered by brief (10 ms) depolarizing current injections, and a few cells had properties indicative for endogenous pacemakers. 5. From 7 DIC on, all cells responded to GABA and to the GABA agonist muscimol. Under voltage clamp, zero current potential depended on the Cl gradient across the membrane and corresponded to the zero current potential of picrotoxin-sensitive postsynaptic currents. 6. After 21 DIC all cells responded to glutamate and its agonist quisqualate. Under voltage clamp, nanomolar concentrations of quisqualate (100-500 nM) induced long-lasting inward currents, which did not decay substantially during prolonged drug application. Quisqualate concentrations greater than 1 microM induced a diphasic inward-current response consisting of an initial fast current transient followed by a maintained current component. With internal Cs replacing K and Na and external TTX (0.3 microM), both current components reversed sign at approximately 8 mV, as predicted by the Nernst equation for currents through channels that were permeable for monovalent cations. 7. Focal applications of GABA and muscimol elicited larger currents when applied near the soma than when applied to the dendrites.(ABSTRACT TRUNCATED AT 400 WORDS)
Gesehen am 08.04.2021